Energetically enhanced natural gas liquefaction process with CO2 precooling. (May 2022) - Waqar, Muhammad; Ishaq, Haris; Jamil, Shah Rukh
Highlights: A novel NG liquefaction process by nitrogen single expander technology is proposed. The new components are integrated for better thermal management and improved efficiencies. The proposed system is optimized using Aspen HYSYS process simulation software. Results showed 7% reduction in unit energy consumption from 9.90 to 9.216 kW·h·kmol −1 . Exergy analysis revealed the reduction in exergy destruction from 17.32 kW to 15.711 kW. Abstract: Natural gas releases 45–50% less CO2 emissions as compared with coal and the liquefaction process is employed for storage and transport of liquefied natural gas that is an energy-intensive process. Numerous scientific efforts are being directed to reduce the energy consumption in the natural gas liquefaction process and to increase the process efficiency. Thus, this study proposes a uniquely modified and energetically enhanced small-scale natural gas liquefaction process by nitrogen single expander technology with CO2 precooling. The novelty of the designed liquefaction process is that the designed configuration does not only reduces the energy consumption of the liquefaction process but also improves the process efficiency. The proposed system is simulated and optimized using ASPEN HYSYS by different design key parameters, and energy consumption has been considered as a key function for the optimization of this cycle. Detailed characterization shows the energy consumption of 9.216 kWh·kmol −1 at a liquefaction rate of 0.77. Furthermore, the effect of pressure output of the valve on unit energy consumption and liquefaction rate is also observed and discussed. It has been observed that by decreasing the valve output pressure, the liquefaction rate decreases and energy consumption increases. Besides, the versatility of this cycle under various pressures, temperatures and composition of methane and other components in the feed gas are considered and effects of these parameters variation on system performance have been observed. The exergy destruction of each equipment is evaluated and investigated in detail for the optimization of results. Results are compared and it shows a 6.90% and 9.0% decrease of unit energy consumption and exergy as compared to referenced base cycle. The performance of numerous relationships is derived from the proposed study and compared with simulated referenced published data. By using energy consumption and liquefaction rate of compared LNG cycles, the maximum error is +0.93 and the minimum error is −0.12. Due to safe and simple operation, compact device, proposed liquefaction process shows a suitable application for development of small-scale, especially for offshore reserves.